Marketing Strategy of Sambal Tari Crackers Business in Improving Family Economy According to Islamic Economic Perspective - Harahap, Junda; Amsal Nasution, Muhammad; Maulana Harahap, Amhar; Jaleha, Siti; Efrida Nasution, Enni; Lubis, Aminah (Fakultas Ekonomi dan Bisnis Islam, 2025)
This study aims to determine the business marketing strategy from an Islamic economic perspective and the marketing strategy of the dance chili crackers business in improving the family economy from an Islamic economic perspective in Neighborhood IV Sibuhuan Market. The research conducted by the author is field research (field research) which is directly related to the object under study. The method used in this research is descriptive qualitative method. While the object of research is the marketing strategy of Sambal Tari crackers in improving the family economy according to an Islamic economic perspective. Based on the results of research and discussion in this study, it can be concluded that business marketing strategies in the perspective of Islamic economics are: 1) Sambal Tari Crackers Business Owners in Neighborhood IV Sibuhuan Market have been true and honest while doing business, 2). They have explained frankly about the price of the merchandise sold, 3) have the nature of fathanah, namely all activities in the management of a company must be intelligent, by optimizing all the potential of the existing mind to achieve the desired goals of the company